Bactericidal Activity and Postantibiotic Effect of Levofloxacin against Anaerobes - Pendland, Susan L. (American Society for Microbiology, 1999)
The bactericidal activity and postantibiotic effect (PAE) of levofloxacin against nine anaerobes were determined. Levofloxacin at concentrations of the MIC and twice the MIC was bactericidal at 24 h to five of nine and nine of nine strains, respectively. The PAE of levofloxacin following a 2-h exposure ranged from 0.06 to 2.88 h.